System Analysis and Comparison Between a 2 MW Conventional Liquid Cooling System and a Novel Two-Phase Cooling System for Fuel Cell-Powered Aircraft - Gerner, H.J. van; Luten, T.; Resende, W.; Mühlthaler, G.; Buntz, M.B. (My University, 2025)
Hydrogen-powered fuel cells are the preferred energy source for electric aircraft. However, for aircraft applications, it is of upmost importance to reduce the mass of the fuel cell system. A considerable amount of the total system mass is due to the fuel cell cooling system. In this paper, the analysis of a 2 MW cooling system for fuel cell-powered aircraft is discussed. A detailed comparison is made between a conventional liquid cooling system with ethylene glycol–water (EGW) and a novel two-phase cooling system that uses the evaporation of a liquid to remove waste heat from the fuel cells. For this novel two-phase cooling system, several refrigerants were analyzed, and methanol resulted in the lowest system mass. The mass of a liquid EGW system is 35% higher than for two-phase methanol with accumulator and 2.4 times higher than for two-phase methanol without accumulator. Because of this large mass benefit, a demonstrator for a two-phase methanol cooling system without accumulator with a capacity of 200 kW is currently being built.